The pedagogical role in J. G. Fichte’s Second Transcendental System of Jena - Ferrán, Feyie (Resonancias. Revista de Filosofía, 2023)
This paper seeks to show the pedagogical role of the concept of summons in the second transcendental system developed by Fichte in Jena. According to the first paragraphs of his Grundlage des Naturrechts the constitution of individual self-consciousness has as a necessary condition that a rational being relates to another by admitting him as a fellow being. That is to say, this relation is constituted by a reciprocal recognition which, at the same time, is the basis of the concepts of right and freedom. To explain the origin of this relationship, Fichte introduces the concept of summons insofar as it is an invitation to participate in rational agency. It will be argued that this concept has a pedagogical role that seeks to promote mutual understanding between rational beings and the constitution of individuals as beings belonging to a community of free beings.